Plus ça change. Reporting rape in the 1990s - Temkin, Jennifer (The British journal of criminology, 1997)
In the 1980s, in the wake of growing public concern, changes were made to police procedures for dealing with complaints of rape. Academic research into the experience of women who reported rape to the police after these changes were instituted, is almost non-existent. This article is based on the findings of a qualitative study of a group of women whose cases were recorded as rape by the Sussex police between 1991 and 1993. It looks at their response to their contact with the police at each phase of the criminal justice process from reporting through to the trial where this occurred. It also considers the overall attitude of victims to the handling of their cases by the police and examines those aspects which were particularly positive or negative. It concludes that, while there is much good practice, the task of improving services for rape victims is not yet complete